Biocatalytic Synthesis of Allylic and Allenyl Sulfides through a Myoglobin‐Catalyzed Doyle–Kirmse Reaction. Issue 43 (20th September 2016) - Tyagi, Vikas; Sreenilayam, Gopeekrishnan; Bajaj, Priyanka; Tinoco, Antonio; Fasan, Rudi
Abstract: The first example of a biocatalytic [2, 3]‐sigmatropic rearrangement reaction involving allylic sulfides and diazo reagents (Doyle–Kirmse reaction) is reported. Engineered variants of sperm whale myoglobin catalyze this synthetically valuable C−C bond‐forming transformation with high efficiency and product conversions across a variety of sulfide substrates (e.g., aryl‐, benzyl‐, and alkyl‐substituted allylic sulfides) and α‐diazo esters. Moreover, the scope of this myoglobin‐mediated transformation could be extended to the conversion of propargylic sulfides to give substituted allenes. Active‐site mutations proved effective in enhancing the catalytic efficiency of the hemoprotein in these reactions as well as modulating the enantioselectivity, resulting in the identification of the myoglobin variant Mb(L29S, H64V, V68F), which is capable of mediating asymmetric Doyle–Kirmse reactions with an enantiomeric excess up to 71 %. This work extends the toolbox of currently available biocatalytic strategies for the asymmetric formation of carbon–carbon bonds. Abstract : Biocatalytic Doyle‐Kirmse reaction : Engineered variants of sperm whale myoglobin catalyze the tandem sulfur ylide formation/[2, 3]‐sigmatropic rearrangement of allylic and propargylic sulfides in the presence of α‐diazo esters. This transformation can be applied to a variety of aryl, benzylic, and alkyl sulfide substrates, and gives high product conversion and enantioselectivity up to 71 % ee .